How to outrun your parasites (or mutualists): symbiont transmission mode is key. Issue 11 (16th September 2022) - Shaw, Allison K.
Abstract : Interspecific interactions shape how and when species, and population, ranges change. Natural enemies, like parasites, can slow population spread, or, conversely, a population can 'outrun' its enemies and spread uninhibited. Yet, less is known about how mutualistic interactions shape population spread, and what role outrunning mutualistic partners plays. Here, I examine host–symbiont interactions specifically; common across animals and plants, and spanning the spectrum from parasitism to mutualism. I develop a model to determine when a symbiont shapes its host's population spread versus when the host outruns its symbiont. I find that symbiont transmission mode is key. For density‐dependent transmission, symbionts cannot be sustained at the low‐density population edge and the host outruns its symbiont, whereas frequency‐dependent transmission leads to symbionts affecting host spread. However, this pattern breaks down in the presence of a host Allee effect: spread dynamics switch from 'pulled' to 'pushed', enabling a symbiont to influence population spread from behind the range edge. Overall, mutualistic symbionts speed up (and parasitic symbionts slow down) host population spread. These findings indicate that contact structures within a population, which shape symbiont transmission, are critical for determining whether host–symbiont interactions influence population spread.